Optimization and techno-economic analysis of photovoltaic-wind-battery based hybrid system. (December 2020) - Anoune, Kamal; Ghazi, Mohamed; Bouya, Mohsine; Laknizi, Azzeddine; Ghazouani, Mokhtar; Abdellah, Abdellatif Ben; Astito, Abdelali
Highlights: Sizing-optimization of a multi-source renewable system using the genetic algorithm. Optimized configuration of PWHS and its energy exchange analysis was provided. Study of different effects of the LPSP ratio on the optimal size of PWHS. Desired LPSP was reached with LCE=0.1915 $/kWh. The results confirm that at least 96.32% of estimated PWHS production was achieved. Abstract: This research work focuses on a sizing-optimization of a hybrid multi-sources renewable energy system with electrochemical storage; these multi-sources are designed to supply the load demand of an industrial prototype. A heuristic approach based on a genetic algorithm is developed and programmed into MATLAB to solve the sizing-optimization problem. The objective function was considered by providing two minimums, namely the levelized cost of energy (LCE) and the loss of power supply probability (LPSP). Sizing-optimization solutions are obtained and analyzed using a time series energy exchange during a representative week in each season to decide the appropriate component size of a PV-Wind based hybrid system (PWHS). The lowest LPSP ratio corresponds to the higher LCE value and the opposite too. The optimal economic solution was: LCE= 0.1915 $/kWh for a given LPSP value, the correspondent PWHS configuration is composed of 9.5 kWp of PV panels, 1 kW of the wind turbine generator and 6.5 kWh of batteries capacities, thus represent a total present value (TPV) equal to 39541$. The experimental results occurred during a week in autumn; the measured energy flow of optimal PWHS configuration confirm at least 96.32% of the estimated energy production is reached.